Applications of Microalgae-Based Technology in Environmental Engineering - Huang , Yaqi Li, He (International Journal of Scientific Research and Management (IJSRM), 2020)
This article outlines the current applications of microalgae-based technology in the three major areas of environmental engineering, which are wastewater treatment, greenhouse gas emission reduction and biomass energy. Briefly explains the mechanism of microalgae removal of pollutants and the current problems. In addition, the view that the three directions could be combined in the future research is pointed out, so as to provide a basis for microalgae to play its greatest role in the field of environment.